Death by Appointment : A Rational Guide to the Assisted Dying Debate. - Finlay, Ilora (Cambridge Scholars Publisher, 2020)
This is a book about a controversial issue--whether doctors should be licensed by law to supply lethal drugs to terminally ill patients. It is written primarily for those who want to find a path through the thickets of a subject that transcends many fields of expertise. The authors have considerable experience of the matters about which they write, involving both research and hands-on medical care of dying people. They are not neutral about 'assisted dying': they are not convinced that the law is in need of change. However, the book employs an evidence-based approach and brings much-needed cla.